EFFECT OF EDUCATION AND OCCUPATION ON THE QUANTITY OF RESEARCH - Joni Maulindar; Zalizah Binti Awang Long; Jawahir Che Mustapha Yusuf (LPPM Universitas Duta Bangsa Surakarta, 2022)
The low interest in research in several places, especially in Indonesia, is influenced by several factors. This study identifies the validity of two factors that can affect the number of lecturers' research. The goal to be achieved in this research is to find out how much education and job title affect the number of lecturers' research. The research was conducted using descriptive quantitative methods with 41 samples of respondents. The results of this study indicate that based on the ANOVA test, the F value is 1.864 with a sig. 0.169. In the regression test, the t value was obtained at 1.153 with a sig value. 0.256 and 0.067. Through this value, it can be concluded that education and job position has a significant effect on the quantity of lecturer research.